Fermentation of phytic acid from lamtoro gung seeds (Leucaena leucocephala) to produce inositol and tannin as pharmaceutical commodity (Medical Journal of Indonesia, 2003)
The research was done to define the effect of tempe yeast concentration on inositol and tannin contents of fermented lamtoro gung seeds (Leucaena leucocephala). This is a research with completely randomized design using four doses of tempe yeast, i.e. 0 %, 5 %, 10 %, and 15 %. Each treatment was replicated 4 times. The resulted data were analyzed by analysis of variance and the significant differences were tested by least significantly difference test. Tannin was analyzed by Lowenthal-Procter method. The result of the research showed that the treatment had significant effects (P<0.05) on the parameter measured. The highest inositol with lowest tannin contents were found by using 15 % tempe yeast and duration of fermentation 96 hours, that is 0.2631 %. (Med J Indones 2003; 12: 236-42)